SOIL TRANSMITTED HELMINTH INFECTION AND EOSINOFIL COUNT IN STUDENTS OF PRIMARY SCHOOL - Ririh Jatmi Wikandari; Nurul Qomariyah; Sunarto Sunarto (Poltekkes Kemenkes Semarang, 2020)
Helminth infections are common in children. This infection attacks more children because their activities are more related to the soil, and the child's diet does not recognize hygiene and hygienic food quality. Diagnosis is done by stool examination to find helminth eggs, can also be supported by eosinophil examination. The purpose of this study was to determine the relationship of helminthiasis with the number of peripheral blood eosinophils in student’s elementary school Gebangsari 01. This study was an observational study using a cross-sectional approach. The population was 40 students in grades 3 and 4. The sample is a total population of 40 people. Fourteen students were not infected with soil transmitted helminth and the eosinophil count was normal. Most students have a clean and healthy lifestyle until 100% negative worm infections. There is no relationship between behavior with the number of eosinophils of student’s in elementary school Gebangsari 01.